Transsexuality and health demands: representations of nursing students - Ana Beatriz Azevedo Queiroz; Alison Malheiros de Castro; Ana Luiza de Oliveira Carvalho; Carina Bulcão Pinto; Juliana da Fonsêca Bezerra; Diana da Silva Gonçalves; Gabriela Silva dos Santos; Hannah de Melo dos Santos (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To analyze the social representations of nursing students about transsexuality and the health demands of transsexual people. Methods: Qualitative, descriptive research with undergraduate nursing students from a public university in Rio de Janeiro/Brazil. The data came from a semi-structured interview and lexical analysis using Alceste 2012 software. Results: Transsexuality was represented as a transgression, with the transsexual person being objectified as unnatural because they do not identify with their biological sex. Hormone therapy and sex reassignment surgeries were understood as the main demands, being anchored in a pathologizing and medicalizing health sphere. However, the theme is not addressed during graduation, generating unpreparedness for professional life. Final considerations: The need to update the academic curriculum, as well as the way of thinking about the care of transsexual people, is essential and urgent for an integral and equitable care.